A Case Study on Staff Perspectives of Programming in a Forensic Mental Health Treatment Facility. - Messina, Emily S.; Yoshitaka Iwasaki (Therapeutic Recreation Journal, 2017)
This paper examines staff impressions of and insights regarding programming at a forensic mental health facility in the Southeastern United States. The facility studied for this research provides services for adult males who are incompetent to proceed to trial or not guilty by reason of insanity. The facility underwent an overhaul of services, transitioning from a voluntary referral-based activity program to a compulsory, structured activity program. This transition offered a unique opportunity to explore staff perceptions of the differences between the two programs. This paper describes the results from a series of focused interviews conducted with employees. The following themes were identified as key issues across staff interviews: (a) value of therapeutic activities, (b) accessibility, (c) choice, (d) participation, and (e) structure. These frontline perspectives offer valuable insights into programming issues for this population.